THE FINANCING OF INFORMATION SECURITY MANAGEMENT IN ENTITIES PERFORMING MEDICAL ACTIVITIES - Lisiak-Felicka, Dominika; Nowak, Paweł A.; Szmit, Maciej; Zajdel, Radosław (Management and Administration Journal, 2021)
All healthcare organizations process “sensitive data” that needs special protection. To ensure an appropriate level of security for this data, it is necessary to allocate adequate financial resources for security measures. The exploratory aim of the research here is the recognition of the current state of information security management systems in selected entities performing medical activities. An analysis and evaluation of these systems and the financing of information security were conducted. The methods and techniques used in the research are Computer Assisted Telephone Interviews, literature studies, and a questionnaire survey with applications for access to public information. The subjects of the research were medical entities subordinate to the local governments of three Polish voivodeships (Łódź, Świętokrzyskie and Pomeranian). The research was conducted between 2017 and 2018. Research findings show that the surveyed entities did not properly manage information security and did not allocate adequate financial resources to ensure information security. The lack of efficient information security management in medical entities may entail negative consequences in the future.